Synthesis Of Silver Nanoparticles Using Kyllinga Brevifolia Extract And Immobilisation On Tio2 Nanotubes For Methyl Blue Dye Removal - Isa, Norain (2020)
The textile industry is an intesive producer of wastewater which unless treated may result in the discharged of toxic and harmful dyes to the environment. One method that can be used to remove dyes is by reduction on a surface of catalyst. The catalyst chosen in this work was silver nanoparticles (AgNPs) synthesised by salt reduction technique. The first part of this thesis focused on the synthesis process of AgNPs. However instead of using typical reductant, AgNPs were synthesised by green chemical route utilising Kyllinga brevifolia extract (KBE) as reducing agent. The KBE was also found to be a good capping as well as stabilizing agent. By controlling the temperature, concentration of AgNO3 as the silver precursor, concentration of KBE and reaction time, the AgNPs were sucsessfully synthesised. The phytochemical constituents in KBE responsible for Ag+ reduction were identified. Carbohydrate, protein, plant sterol (stigmasterol and campesterol) were found to have the highest concentration thus proposed as the main constituents that can reduce Ag+ ions to Ago. KBE derived AgNPs are highly dispersed with ~ 17.64 nm diameter and have quasi-spherical shape. The catalytic removal of MB was then done to demonstrate the properties of AgNPs in removing MB. Four (4) systems were used to investigate the performance of AgNPs; System 1 (AgNPs alone), System 2 (AgNPs + NaBH4), System 3 (AgNPs + KBE) and System 4 (AgNPs on TNTs). From the catalytic study on MB removal, no reduction was observed in System 1. Reduction was the highest in System 2. The pseudo first and second order approaches were used for the kinetic study of System 2. 100% removal efficiency (%RE) was found to be possible in 30 ppm MB solution with pH 8-10 which followed first order kinetic with reaction rate of 2.5715 min-1. For 100 pm solution, the first order kinetic was 1.4614 min-1. It took less than 5 mins for the 100% removal which is considered to be extremely fast. On the other hand, for System 3, 93 %RE of MB was achieved with a rate of reaction of 0.2663 min−1 at pH 2. The efficient removal is proposed to be due to the process of reduction occuring via electron relay effect whereas in System 3, sedimentation occurred along with the reduction process. However, at the end of the process it was observed that seperation of AgNPs from the treated MB solution was difficult which may pose a secondary pollution. In order to circumvent this, in the second part of this thesis, System 4 was introduced where AgNPs were immobilised on TiO2 before being subjected to be used as catalyst for MB removal. The TiO2 was fabricated on a surface of titanium wire by anodic process. The anodic film was made to be in a form of TiO2 nanotube (TNT) arrays and AgNPs were then dispersed on the TNTs as catalyst support by wet impregnation technique. The TNTs/AgNPs were characterized and their catalytic activity was tested for removal of MB. However, it was found that the removal efficiency was much slower as compared to when AgNPS were used. The reduction of MB by TNTs/AgNPs followed pseudo-first order kinetic with the kinetic rate of 7.5 x 10-3 min-1.